Economic Impacts of Agricultural and Natural Resource Industries in Florida, 2003 - Alan W. Hodges; W. David Mulkey (EDIS, 2019)
This is EDIS document FE627, a publication of the Food and Resource Economics Department, UF/IFAS Extension. Published February 2006.